2015
DOI: 10.1159/000431292
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body MRI in the Staging of Esophageal Cancer - A Prospective Comparison with Whole Body <sup>18</sup>F-FDG PET-CT

Abstract: Background: Positron emission tomography and computed tomography (PET-CT) is established in the staging of esophageal cancer. In this study, an MRI protocol was designed to emulate the anatomical (T1-weighed (T1W) and T2W imaging) and functional information (diffusion-weighted imaging) provided by PET-CT. Methods: In all, 49 patients with carcinoma of the esophagus underwent PET-CT and whole-body MRI (WBMRI). WBMRI was carried out using dedicated sequences tailored to detect metastatic disease at each area cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…On magnetic resonance imaging (MRI) routine nonenhanced T 1 ‐weighted imaging and T 2 ‐weighted imaging can be used to evaluate the esophageal wall invasion. But both of them fail to provide a prediction of histologic grade …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On magnetic resonance imaging (MRI) routine nonenhanced T 1 ‐weighted imaging and T 2 ‐weighted imaging can be used to evaluate the esophageal wall invasion. But both of them fail to provide a prediction of histologic grade …”
mentioning
confidence: 99%
“…But both of them fail to provide a prediction of histologic grade. [10][11][12][13][14][15] Diffusion-weighted imaging (DWI) is a noninvasive approach to probe molecular diffusion of water on the microscopic scale without contrast administration, 16,17 and the diffusion of water can be quantitatively described by the apparent diffusion coefficient (ADC). Recently, a few studies have demonstrated that DWI along with ADC measurement is helpful in detecting, characterizing, and staging malignant lesions.…”
mentioning
confidence: 99%
“…In radiotherapy, the uptake of FLT is related to the proliferating cell nuclear antigen; thus the FLT can evaluate the efficacy of radiotherapy; so, this has more sensitive than FDG [31,32]. Many semi-quantitative methods are widely used to define the threshold range of the SUV in the PET/CT image [14,33,34]. Nevertheless, whether it is 18 F-FDG or 18 F-FLT PET-CT, the suitable SUV range to delineate the target volume has not yet been clearly defined [35].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with PET/CT, WBMRI has similar accuracy in detecting the primary tumor, nodal deposits, and metastatic disease. In a study done by [14], the PET-CT and WBMRI detected the primary tumor in 46 of 49 (94%) and 48 of 49 (98%) patients, respectively. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of nodal metastasis detection in patients undergoing surgery (n = 18) were 27%, 100%, 100%, 47%, and 56% for PET-CT compared with 30%, 100%, 100%, 53%, and 61% for WBMRI.…”
Section: Limitations Of the Studymentioning
confidence: 98%